The Relative Handgrip Strength and Risk of Cardiometabolic Disorders: A Prospective Study - Hao, Guang; Chen, Haiyan; Ying, Yuting; Wu, Min; Yang, Guang; Jing, Chunxia (Frontiers in Physiology, 2020)
Background This study aims to investigate the association between handgrip strength (HGS) and cardiometabolic disorders (CMD), including hypertension, diabetes, and dyslipidemia, in a prospective study. Methods The association between HGS and CMD was examined using the data from 5,271 Chinese adult participants ≥45 years old enrolled in the CHARLS (Chinese Health and Retirement Prospective Cohort Study) during 2011–2015. Relative HGS, calculated as maximal absolute HGS from both hands divided by body mass index, was used in the primary analysis and divided into three groups according to the tertiles (T1, T2, and T3). Results The participants with higher relative HGS had a lower risk of hypertension, diabetes, and dyslipidemia than those with lower HGS, although did not reach statistical significance for diabetes and hypertension in males. Participants with higher HGS had significantly lower risk of hypertension [T3 vs. T1: OR = 0.69, 95% CI = 0.51–0.91, P = 0.010] and dyslipidemia (OR = 0.65, 95% CI = 0.51–0.83, P < 0.001) in males. For females, participants with higher HGS had significantly lower risks of dyslipidemia (OR = 0.67, 95% CI = 0.54–0.83, P < 0.001). Conclusion A consistent association was observed between higher relative HGS and lower risk of CMD. Further research is required to evaluate whether relative HGS can be a convincing predictor for the occurrence of CMD and as a target for intervention in the high-risk population.